Effect of supplementing graded levels of organic and inorganic chromium on the performance and anti-oxidant status in commercial broilers - reddy, eevuri tirupathi (Indian Journal of Animal Nutrition, 2018)
The present experiment was conducted to study the effects of inclusion of graded levels of organic and inorganic chromium (Cr) at 0, 300, 600, 900, 1200 and 1500 µg/kg of diet, separately in a 5 x 2 factorial manner on the performance and anti-oxidant status of broilers. A total of 440 day-old commercial broiler male chicks were divided into 11 dietary treatments with 8 replicates (5 broilers in each replicate) and fed test diets ad-lib from day-one to 42 days of age (pre-starter 0-14 d, starter 15-28 d and finisher 29-42 d). Feed intake (FI) was more (P<0.05) in organic Cr fed group and at a level of 600 µg broilers consumed more (P<0.05) feed compared to other levels. The interaction (source and level) had significantly increased the FI compared to control. Body weight gain (BWG) of broilers was not influenced by the source of Cr. However, no significant difference was observed in BWG with levels above 600 µg. The interaction effect improved (P<0.05) the BWG than control group. The feed conversion ratio (FCR) was improved in Cr supplemented diets, however, supplementation of Cr at 1500 µg/kg significantly improved the FCR. Supplementation of Cr at graded levels had reduced (P<0.05) the malondialdehyde (MDA) levels; decreased the glutathione peroxidase (GSH-PX) activity and Heterophil to Lymphocyte (H/L) ratios. Based on present investigation, it can be concluded that supplementation of either organic or inorganic Cr at 600 µg/kg diet was found enough in terms of growth performance and antioxidant status in broilers.